Higher food prices can reduce poverty and stimulate growth in food production - Headey, Derek D.; Hirvonen, Kalle (Nature Publishing Group, 2023)
Food prices spiked sharply in 2007–2008, in 2010–2011 and again in 2021–2022. However, the impacts of these spikes on poverty remain controversial; while food is a large expense for the poor, many poor people also earn income from producing or marketing food, and higher prices should incentivize greater food production. Short-run simulation models assume away production and wage adjustments, and probably underestimate food production by the poor. Here we analyse annual data on poverty rates, real food price changes and food production growth for 33 middle-income countries from 2000 to 2019 based on World Bank poverty measures. Panel regressions show that year-on-year increases in the real price of food predict reductions in the US$3.20-per-day poverty headcount, except in more urban or non-agrarian countries. A plausible explanation is that rising food prices stimulate short-run agricultural supply responses that induce increased demand for unskilled labour and increases in wages. Main